PERSONAL PROPERTY SECURITY INTERESTS ON LANDS RESERVED FOR FIRST NATIONS - Hitchings, Scott (2020)
In this thesis I examine the issues encountered by First Nations persons and bands when attempting to use assets that are personal property, as defined by the Personal Property Security Act, 1993 and similar Acts in Canadian jurisdictions, as security in secured financing arrangements. Subsection 89(1) of the Indian Act prohibits personal property of a First Nation person or band that is located on reserved lands from acting as collateral, unless it is in favour of another First Nation person or band. The result of this subsection has been that First Nation persons and bands have limited access to credit for personal or business purposes. I argue that a solution needs to be found to this problem. The solution could take the form of legislative reform from comprehensive changes to the systems regulating secured transactions on First Nations reserved lands, to more simple changes that allow a First Nation person or band to waive the application of the section to their transaction or property. Another solution I explore is that a line of jurisprudence in which a commercial exception has been considered is accepted to be valid law, which would allow First Nation persons and bands to operate under the presumption that commercial assets are exempt from the Indian Act prohibition.